European integration of the agricultural sector of Ukraine: challenges and prospects of fulfilling obligations - Galan, V. O.; Samoilova, A. R. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
The article is dedicated to a comprehensive analysis of the European integration of Ukraine’s agricultural sector, highlighting the challenges and prospects encountered along this path. The author emphasizes the growing urgency of integration processes in the context of the full-scale aggression by the Russian Federation, which makes Ukraine’s accession to the EU a top priority of state policy. The study examines the historical background of Ukraine-EU relations, beginning with the official declaration of Ukraine’s intention to develop relations with the EU as outlined in the Resolution of the Verkhovna Rada of Ukraine dated July 2, 1993, «On the Main Directions of Ukraine’s Foreign Policy,» as well as the EU’s recognition of Ukraine’s independence in December 1991. Key legal instruments that shaped Ukraine’s course toward European integration are analyzed, in particular, the Partnership and Cooperation Agreement between Ukraine and the EU signed on June 14, 1994, which laid the first legal foundations for cooperation, and the Association Agreement between Ukraine and the EU signed in 2014. The article underscores that the Association Agreement obliges Ukraine to gradually implement European norms and requirements in areas such as food safety, pesticide control, animal welfare, increased competitiveness of the agricultural sector, improved market transparency and efficiency, and the creation of favorable investment conditions. Considerable attention is given to the Common Agricultural Policy (CAP) of the EU, viewed as a benchmark for adapting Ukraine’s agricultural policy. CAP represents a supranational framework of measures aimed at developing sustainable and competitive agriculture. The author notes that Ukraine demonstrates political will and institutional readiness for large-scale transformations, as evidenced by the intensification of legislative harmonization with the acquis communautaire following Ukraine’s acquisition of EU candidate status in June 2022. A SWOT analysis is conducted, identifying the strengths, weaknesses, opportunities, and threats of Ukraine’s agricultural sector. The article concludes that the success of integration depends on Ukraine’s ability to enhance competitiveness, harmonize legislation, and strike a balance between national interests and EU requirements.